Lexical Verb(s) of Hedging Used by The White House Secretary’s Responses in Press Briefing - Humairotul Husna; Mohammad Masrukhi (Eduvest - Journal of Universal Studies, 2023)
The study aims to investigate the lexical verbs of hedging used by two White House secretaries in press briefings, namely Jen Psaki (JP) and Karine Jean Pierre (KJP). The research focuses on the secretary's response in answering the question made by journalists. The corpus consisting of 22 press briefing meetings published from November 2021 to August 2022. The study identifies the most used lexical verbs by the two secretaries through quantitative analysis and qualitative analysis to describe their functions. As a result, the use of hedging verbs is more widely used by secretary Jen Psaki than secretary Karine Jean Pierre. Nevertheless, both used many verbs in the form of think in their responses. The findings reveal the uncertainty and reduce the secretary’s commitment. Besides, the function of hedging is to protect secretaries from forward-looking statements and seek protection against overstatement.